A study of safety performance in building maintenance works / M. Syahir Hadi Mohd Shaharuddin - Mohd Shaharuddin, M. Syahir Hadi (2012)
Building maintenance works usually involve inspecting or testing workplace, building and other facilities, work equipment or mean of transport, and servicing, adjusting, repairing or replacing them. Building maintenance works can easy to overlook. But without regular maintenance or experience, thing can go wrong that can cause death or serious injury. Even small pieces of equipment, if they are not well maintenance can cause serious problem in the future. These problems can affect not only the maintenance workers directly involved, but also to other workers and even occupant of the building or public. Due to these problems, safety practice and regulation are very important in every building maintenance works. Building maintenance contractor must consider safety practice or safety factor in operating building maintenance works. This research will identify the most safety factor that affect the performance of building maintenance contractor in performing maintenance works. A survey will be conducts on safety performance factor among the building maintenance contractor in Penang, Perak and Selangor.